Effects of ascorbic acid on human hepatoma cell proliferation and redifferentiation. - Kang Jiu-hong; Shi Yi-min; Zheng Rong-liang (Acta Pharmacologica Sinica, 2016)
AIM: To examine the effects of ascorbic acid (AA) on hepatoma. METHODS: Choosing an all-trans tretinoin (Tre) as a positive control, cell growth, and cell redifferentiation tests by cell surface charges, biochemical changes, and cell growth in soft agar were measured. RESULTS: After being treated with AA 6 mmol.L-1, the growth curve and mitotic index of human hepatoma cells decreased remarkably, the cellular growth inhibitory rate amounted to 58.9%. The indices related with cell malignancy alleviated, such as cell surface charge obviously decreased, the electrophoresis rate dropped from 1.64 microns.s-1.V-1.cm-1 to 0.93, the average value of alpha-fetoprotein (alpha-FP) content decreased from 302 micrograms.g-1(protein) to 90, and gamma-glytamyl-transpeptidase (gamma-GT) activity from 0.81 U.g-1(protein) to 0.16. The index related with cell differentiation increased, such as the average level of tyrosine-alpha-ketoglutarate transminase activity increased from 10.3 micromol.g-1(protein) to 41.2, and the colonogenic potential decreased 94.4%. CONCLUSION: AA can inhibit human hepatoma cells proliferation, induce redifferentiation, and reverse its malignant phenotypic characteristics.